PSIKOLOGI TOKOH FANTON DRUMMOND DALAM NOVEL OLENKA KARYA BUDI DARMA TAHUN PELAJARAN 2012/2013 - Solanda, Marfia; Bahardur, Iswadi; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2013)
This research is distributed by the conflict in and around the maze of life of a character named Fanton Drummond are often faced with a less supportive environment desires. Formulation of this research is "how the psychology of character in a novel Olenka Fanton Drummond works Budi Darma review of aspects of the id, ego, and superego?" The purpose of this study is to describe and explain the conflict of the main character works Budi Darma novel Olenka review of aspects of the id, ego, and superego using the theory proposed by Sigmund Freud.This research is a qualitative study using descriptive methods. The data in this study in the form of text and dialogue monologue sentences. Data sources of this study is novel Olenka Budi Darma work. The research was carried out by stages: (1) read and understand the novel Olenka work Budi Darma, (2) identify and classify the data contained in the novel Olenka work Budi Darma, (3) determine the aspects of the conflict of the id, ego, and superego, (4 ) analyzing the data, (5) prove and formulate conclusions.Analysis of the data showed that the main character (Fanton Drummond) conflict, (1) aspects of id make Fanton Drummond has desires that are wild and not terkonrol to Olenka and MC, (2) aspects of the ego makes Fanton Drummond became hard to maintain figure impact on the opinion itself, (3) aspects of the superego made aware of his mistake Fanton Drummond who maintains his ego has been to make Fanton Drummond stuck into a variety of difficult situations. Suggestions in this study are not expected for readers concerned with the ego, and the balance between the id, ego, and superego.